Immunological control of cell cycle aberrations for the avoidance of oncogenesis: the case of tetraploidy. (7th May 2013) - Senovilla, Laura; Galluzzi, Lorenzo; Castedo, Maria; Kroemer, Guido
Abstract : Tetraploid cells—cells that contain twice the normal amount of DNA—are more prone to neoplastic transformation than their normal, diploid counterparts since they are genomically unstable and frequently undergo asymmetric, multipolar cell divisions. Similar to many other genomic aberrations, tetraploidization is normally avoided by multiple, nonredundant cell‐intrinsic mechanisms that are tied to cell cycle checkpoints. Unexpectedly, tetraploidization is also under the control of a cell‐extrinsic mechanism determined by the immune system. Indeed, oncogene‐ or carcinogen‐induced cancers developing in immunodeficient mice contain cells with a higher DNA content than similar tumors growing in immunocompetent hosts. Moreover, cancer cell lines that have been rendered tetraploid in vitro grow normally in immunodeficient mice, yet almost fail to generate tumors in immunocompetent animals. One of the mechanisms whereby the immune system recognizes tetraploid cells originates from tetraploidy causing an endoplasmic reticulum (ER) stress response that culminates in the exposure of the ER protein calreticulin on the cell surface. Hence, tetraploidy exemplifies a potentially oncogenic alteration that is repressed by a combination of cell‐autonomous mechanisms and immunosurveillance. Oncogenesis and tumor progression require the simultaneous failure of both such control systems.